Detecting Outliers Using Modified Recursive PCA Algorithm For Dynamic Streaming Data - Dani, Yasi; Gunawan, Agus Yodi; Khodra, Masayu Leylia; Indratno, Sapto Wahyu (Institute of Automation and Computer Science, Brno University of Technology, 2023)
Outlier analysis has been widely studied and has produced many methods. However, there is still rare a method to detect outliers for dynamically streaming batch data (online learning). In the present research, a novel online algorithm to detect outliers in such dataset is proposed. Data points are proceeded by applying a modified recursive PCA to predict sequentially parameters of the model; eigenvalues and eigenvectors of the statistical detection model are recursively updated using approximate values by perturbation methods. More specifically, the recursive eigenstructure is obtained from the derivation of the covariance matrix using the first-order perturbation technique. The Mahalanobis distance is then used as an outlier score. Our algorithm performances are evaluated using some metrics, namely accuration, precision, recall, F1-score, AUC-PR, and the execution time. Results show that the proposed online outlier detection is computationally efficient in time and the algorithm's performance effectiveness is comparable to that of the offline outlier detection algorithm via classical PCA.
Keywords: Outlier; Online learning; Recursive PCA; Eigendecomposition; Perturbation method